PERANAN PEDAGANG KAKI LIMA DALAM MENANGGULANGI TINGKAT PENGANGGURAN DALAM PERSPEKTIF EKONOMI ISLAM: Studi Kasus Kota Terpadu Mandiri Pasar Giri Kencana Kabupaten Bengkulu Utara - Sunjaya; Agung Cucu Purnawirawan (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2026)
The purpose of this research was to determine the role of street vendors in resolve unemployment in KTM (independent integrated city) Giri Kencana market. In answering the problem, the researcher useda sociological approach. This research was classified as qualitative descriptive research, data is collected by describing, summarizing various conditions, situations or social phenomena that exist in society and efforts to bring that reality to the surface as a characteristic, character, trait, model, sign or description or a particular condition, situation or phenomenon and data analysis was carried out by conducting in-depth interviews with informants. After the interview, the researcher made the result of the interview by writing and playing the recording. And researchers took the appropriate data and ignore the unneeded data. The results of this research were: based on the results of interviews that has been conducted, and has been presented in the results of the research. It was concluded that being a Hawker was the last resort of come societies, due to the insufficient economy of their families, there wer also houswives who later decided to become street vendors in the Giri Kencana market, and with the same goal of providing for household needs, and being a Hawker was an efforts that was considered to reduce the number of unemployed in a place, In Islam trading was a job advocated by the Massenger of Allah SWT and even a explained by Allah in the Qur’an surah al-Jumu’ah verse 10. Humans could be trades, but still apply the rules that has been set. The rules in question were siddiq, amanah, not deceiving, and keeping promises.